Export Performance of Bangladesh: A Study on Selected Products - Mehtaj, Mouri; Junayed, Mohammed (Asian Business Review, 2017)
Export is one of the major components of global business which secures a country’s economic condition to a large extent. Developed as well as developing countries always try to increase their exports for the growth and expansion of their economies. This study indicates the trends of exporting from the early stage of our economic development. For that purpose, tea, raw jute and jute products, fisheries and leather have been chosen to figure out the situation. All the information has been collected from the secondary sources. The findings would be helpful for the government to take necessary strategies and policies for improving the situation.